Infants’ behavioral and physiological profile and mother–infant interaction - Costa, Raquel A. (2012)
This study aims to (a) identify and profile groups of infants according to their behavioral and physiological characteristics, considering their neurobehavioral organization, social withdrawal behavior, and endocrine reactivity to stress, and to (b) analyze group differences in the quality of mother–infant interaction. Ninety seven 8-week-old infants were examined using the Neonatal Behavioral Assessment Scale and the Alarm Distress Baby Scale. Cortisol levels were measured both before and after routine inoculation between 8 and 12 weeks. At 12 to 16 weeks mother–infant interaction was assessed using the Global Rating Scales of Mother–Infant Interaction. Three groups of infants were identified: (a) ‘‘withdrawn’’; (b) ‘‘extroverted’’; (c) ‘‘underaroused.’’ Differences between them were found regarding both infant and mother behaviors in the interaction and the overall quality of mother–infant interaction. The identification of behavioral and physiological profiles in infants is an important step in the study of developmental pathways.